2017
DOI: 10.1590/1807-1929/agriambi.v21n6p363-368
|View full text |Cite
|
Sign up to set email alerts
|

Performance of drippers in two filtering systems using sewage treatment effluent

Abstract: A B S T R A C TThe objective of this study was to evaluate the performance of three models of drippers using treated sewage effluent, pure and diluted, and two types of filters, screen and disc. The treated sewage effluent used in the experiment was collected from the city's treatment plant. The experiment included 12 lateral lines with three types of emitters to apply pure (100%) and diluted (50%) effluent filtered by screen and disc filters. The combination of those factors set the treatments: T1 (50% efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Similarly, we found that coefficient of variation computed at an hourly basis was 1.653% (CI 95% 1.240-2.065%) in the control and 3.587% (CI 95% 2.713-6.444%) in the HF-DLF, with scarce differences among dilution, suggesting that accumulation of deposited material in the emitters affected the dripline flow performance. Such coefficient of variation was lower than those found in other similar studies [28,29] and can be marginally acceptable as indicated by Bodole et al [26], according to which a test duration of more than 60 min is enough to minimize the uncertainty due to the initial fluctuation of the data. The lower variation of the HF-DLF is likely due to an anti-clogging shape of the present emitters if compared to other emitters [30].…”
Section: Discussioncontrasting
confidence: 50%
“…Similarly, we found that coefficient of variation computed at an hourly basis was 1.653% (CI 95% 1.240-2.065%) in the control and 3.587% (CI 95% 2.713-6.444%) in the HF-DLF, with scarce differences among dilution, suggesting that accumulation of deposited material in the emitters affected the dripline flow performance. Such coefficient of variation was lower than those found in other similar studies [28,29] and can be marginally acceptable as indicated by Bodole et al [26], according to which a test duration of more than 60 min is enough to minimize the uncertainty due to the initial fluctuation of the data. The lower variation of the HF-DLF is likely due to an anti-clogging shape of the present emitters if compared to other emitters [30].…”
Section: Discussioncontrasting
confidence: 50%